CASE-BASED REASONING PEMILIHAN METODE KONSTRUKSI JALAN DI ATAS TANAH BERMASALAH KEDALAMAN 10 SAMPAI DENGAN 20 METER - maulana Iqbal; Anton Soekiman (Jurnal Infrastruktur, 2020)
Problems with road construction over problematic soils without soil improvement or reinforcement generally will result in embankment instability and settlement. Many road networks over problematic subgrade in some areas in Indonesia experienced significant decrease of service levels before attaining their service life. Lack of understanding of subgrade characteristics results in ineffective and inefficient selection of construction methods. The tendency to choose the method used is still based on budgeting scheme. The selection of road construction methods on subgrade problems with a Case-Based Reasoning (CBR) analysis can save time in making decisions based on expertise of experts, so that the risk of inaccuracies in the method selection results in in approriate decision making can be minimized. Based on the results of analysis by taking case study of Pemalang - Batang toll road at the depth of 10 to 20 meters and using CBR analysis, obtained 97.74% similarity of Prefabricated Vertical Drain (PVD) construction method combined with vacuum preloading and Prefabricated Horizontal Drain (PHD) method.